2001
DOI: 10.1016/s0092-8674(01)00597-9
|View full text |Cite
|
Sign up to set email alerts
|

The Membrane-Anchored MMP Inhibitor RECK Is a Key Regulator of Extracellular Matrix Integrity and Angiogenesis

Abstract: Matrix metalloproteinases (MMPs) are essential for proper extracellular matrix remodeling. We previously found that a membrane-anchored glycoprotein, RECK, negatively regulates MMP-9 and inhibits tumor invasion and metastasis. Here we show that RECK regulates two other MMPs, MMP-2 and MT1-MMP, known to be involved in cancer progression, that mice lacking a functional RECK gene die around E10.5 with defects in collagen fibrils, the basal lamina, and vascular development, and that this phenotype is partially sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
668
0
31

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 631 publications
(744 citation statements)
references
References 43 publications
25
668
0
31
Order By: Relevance
“…Studies have shown that post‐transcriptional RECK can inhibit MT1‐MMP. RECK enables tissues to strengthen remodeling and repairing by maintaining blood vessels and nerve tissue around ECM, which is very important during embryonic development (Liu, Zhou, & Zhu, 2016; Oh et al., 2001). Studies about mouse embryos showed that knocking out RECK gene will lead to death of the mouse embryos at early stages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that post‐transcriptional RECK can inhibit MT1‐MMP. RECK enables tissues to strengthen remodeling and repairing by maintaining blood vessels and nerve tissue around ECM, which is very important during embryonic development (Liu, Zhou, & Zhu, 2016; Oh et al., 2001). Studies about mouse embryos showed that knocking out RECK gene will lead to death of the mouse embryos at early stages.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, MT1‐MMP positive expression was visible on microvascular endothelial cells marked by FVIII–R Ag, which demonstrated that MT1‐MMP has a role in angiogenesis around ischemic area. On the other hand, reversion‐inducing cysteine‐rich protein with Kazalmotifs (RECK) is one of the inhibitor of MT1‐MMP in other models (Silva et al., 2015; Oh et al., 2001), but whether RECK suppress the function of MT1‐MMP in stroke is not clear. This study suggested that treadmill exercise can promote angiogenesis, up‐regulate the expression of MT1‐MMP and down‐regulate the expression of RECK on vascular endothelial cells around cerebral ischemic area.…”
Section: Introductionmentioning
confidence: 99%
“…Reversion-inducing cysteine-rich protein with Kazal motifs (RECK) acts as a membrane-anchored metalloproteinase regulator [1][2][3][4] which functions as a regulator of extracellular matrix integrity in normal condition, contributing to tumor and metastasis suppressing agent. However, recent study found abundant expression of RECK in the cells associated with blood vessels undergoing rapid remodeling in the mouse implantation chambers, suggesting that RECK has a role in vascular remodeling which may involve non-sprouting mechanisms such as intussusception and pruning.…”
Section: Introductionmentioning
confidence: 99%
“…The MMPs, which are known as a family of zincdependent endopeptidases, are essential for normal tissue remodeling [29], and many studies have shown the involvement of MMPs in tumor growth [9], differentiation [12], apoptosis [24], migration, invasion [7], the regulation of tumor angiogenesis [23] and immune surveillance [lo]. One member of the MMP family, MMP-1, is capable of degrading type I, 11, 111, VII, X, gelatin, and aggrecan [8].…”
Section: Introductionmentioning
confidence: 99%